KMP-11: proteína 11 de Membrana de Kinetoplástidos - Diez Ortega, Hugo; Laboratorio de Parasitologia Molecular, Departamento de Microbiología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2004)
The kinetoplastid membrane protein KMP-11 is a 11kDa glycoprotein, is present on the surface of all stages of parasites life cycle, but is expressed  at higher levels in vector insect stages. The characteristics presented by this protein, such as its remarkably high degree of sequence homology  among kinetoplastids, its association to the membrane, as well as to the cytoskeleton and the flagellum, and its immunological reactivity make this protein a potential target for developing chemotherapy or immunotherapy strategies against the diseases caused by these parasites. In this context, here we present the results of the KMP-11 genes study from Trypanosoma rangeli.